MODEL OF PROJECT-BASED AND INTRAPERSONAL AND INTERPERSONAL COMPETENCES-INFUSED LEARNING IN WRITING CLASSES - Astari, Triesa Gina; Iskandar, Ifan; Dewanti, Ratna (BASIS (Bahasa dan Sastra Inggris), 2022)
This study aims to analyze the employment of project-based learning and the accommodation of intrapersonal and interpersonal competences in the existing models of learning in writing classes of English Language Education Study Program. The data were the components of models of learning in five writing courses syllabuses of five different universities along with their teaching and learning activities. A qualitative research design was employed in conducting this study followed by document analysis and observation as the instruments. The result showed that the existing models of learning mostly employed Direct Instruction and Computer-Assisted Instruction which are supported by Behavioral Approach, and Reciprocal Teaching and Scaffolding which are supported by Cognitive Approach. The employment of Project-Based Learning and the accommodation of Intrapersonal & Interpersonal Competences mostly occurred merely in the component of Technique; Teaching and Learning Activities. In employing Project-Based Learning, none of the universities employed Project Manager indicator. Also, in accommodating the Intrapersonal Competences, none of the universities put them to the first component of Approach: Course Description. Whereas the Interpersonal Competences were accommodated to all components of the existing models of learning.